A flame retardant self-adhesive waterproof membrane binder and preparation method thereof

By using modified montmorillonite and quaternary ammonium salt-capped antioxidant hyperbranched polymers in flame retardant self-adhesive waterproof coil cement, the problem of degradation of performance of cementitious materials in the prior art during high temperature and aging is solved. It achieves efficient flame retardant and aging resistance, extending the service life of the coil material.

CN116144320BActive Publication Date: 2025-02-18ANHUI AOJIA BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310170907.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-02-18
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The existing flame retardant self-adhesive waterproof coil cements have deteriorated performance during high temperatures and aging, and contain unhealthy halogen-containing flame retardants, which affects their service life.

Method used

Modified montmorillonite and quaternary ammonium end-capped antioxidant hyperbranched polymers are used as flame retardant components, and radical stability is achieved through the three-dimensional network structure of modified montmorillonite and the free radical stability of quaternary ammonium end-capped antioxidant hyperbranched polymers. and eliminate the effect, improve the high temperature resistance and aging resistance of the cement.

Benefits of technology

It significantly improves the flame retardant and aging resistance of the cement, slows down the reaction of free radical chains during aging, extends the service life of the coil, and avoids unhealthy halogen-containing flame retardants.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flame retardant self-adhesive waterproof coiled material binder and a preparation method thereof, belonging to the technical field of waterproof coiled materials. The binder comprises the following raw materials in parts by weight: 100-110 parts of type I waterproof coiled material asphalt, 5-8 parts of aluminum diethylphosphinate, 2-4 parts of modified montmorillonite, 12-16 parts of SBS, 15-20 parts of waste rubber powder, 16-20 parts of aromatic oil and 10-22 parts of tackifying resin. The preparation steps are as follows: heating the type I waterproof coiled material asphalt to 190-200 DEG C, adding the aromatic oil and stirring evenly, then cooling to 180-190 DEG C, adding SBS and heating to 190-200 DEG C, stirring for 1.5 hours, adding the tackifying resin and the waste rubber powder, keeping warm and stirring for 0.5 hours, then adding aluminum diethylphosphinate and modified montmorillonite, and keeping warm and stirring for 0.5 hours. According to the invention, diethylphosphinate and modified montmorillonite are added to the binder, so as to give the self-adhesive waterproof coiled material binder higher flame retardant performance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waterproof coiled materials, and in particular relates to a flame retardant self-adhesive waterproof coiled material binder and a preparation method thereof. Background Art

[0002] Self-adhesive waterproof membrane binder is an important raw material for the preparation of asphalt waterproof membrane, which is required to have high bonding and waterproof properties. With the development of the market, self-adhesive membranes are becoming more and more popular, so the performance requirements for self-adhesive waterproof membrane binders are getting higher and higher.

[0003] Asphalt is mainly composed of macromolecular hydrocarbons and non-hydrocarbons. Once an accident occurs, asphalt, as a flammable material, will burn violently and release a large amount of toxic gases and salt mist. At the same time, under the combined action of convection and radiation heat transfer, asphalt will continue to burn and release a large amount of heat, making it difficult to extinguish the fire. Therefore, the flame retardant properties of waterproof membrane binders are currently required to be relatively high. For example, Chinese patent CN110760289B discloses a flame retardant self-adhesive waterproof membrane binder, a preparation method thereof, and a waterproof membrane prepared therefrom. The flame retardant self-adhesive waterproof membrane binder is made of the following raw materials in parts by weight: 40-45 parts of type I waterproof membrane asphalt, 2-5 parts of ethylene tar, 4-10 parts of SBS, 8-15 parts of waste rubber powder, 6-10 parts of cyclohexane oil, 3-11 parts of tackifying resin, 4-8 parts of chlorinated paraffin, and 8-20 parts of diatomaceous earth. Although the membrane prepared by the binder has good flame retardant properties, it is the chlorinated paraffin that plays a flame retardant role, which is a halogen-containing flame retardant and is not healthy enough. In addition, when the existing membrane is exposed for a long time, the mineral particles on the surface are easy to fall off and age, resulting in cracks and gaps in the waterproof layer, affecting the service life of the membrane.

[0004] Therefore, it is necessary to provide an aging-resistant, flame-retardant, self-adhesive waterproof membrane binder. Summary of the invention

[0005] The object of the present invention is to provide a flame retardant self-adhesive waterproof membrane binder and a preparation method thereof, so as to solve the problems in the background technology.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A flame retardant self-adhesive waterproofing coiled material binder comprises the following raw materials in parts by weight: 100-110 parts of type I waterproofing coiled material asphalt, 5-8 parts of diethyl aluminum phosphinate, 2-4 parts of modified montmorillonite, 12-16 parts of SBS (styrene-butadiene-styrene block copolymer), 15-20 parts of waste rubber powder, 16-20 parts of aromatic oil, and 10-22 parts of tackifying resin.

[0008] Further, the modified montmorillonite is prepared by the following steps:

[0009] Montmorillonite is added into deionized water for dispersion to form a 5-10wt% suspension, a quaternary ammonium salt-terminated antioxidant hyperbranched polymer is added into a 50wt% ethanol solution, stirred, and then added into the suspension, reacted at 50-60°C for 6-8h, centrifuged after the reaction is completed, and the precipitate is dried at 100°C to constant weight, ground, and modified montmorillonite is obtained; the amount of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is 10-15% of the mass of the montmorillonite, the amount of the ethanol solution is 10 times the mass of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer, the montmorillonite is Na-based montmorillonite, and the cation exchange capacity is 900-1100 mmol / kg.

[0010] Montmorillonite is a layered silicate mineral. Adding it to an asphalt matrix can improve the flame retardant properties of the asphalt matrix. However, it has poor compatibility with the asphalt matrix and is difficult to disperse evenly, which affects the overall performance of the asphalt matrix. The present invention uses a quaternary ammonium salt-terminated antioxidant hyperbranched polymer to modify montmorillonite. By using an ion exchange method, organic matter is introduced into the montmorillonite layer to increase the interlayer spacing, providing more sites for the montmorillonite to combine with the asphalt matrix. The introduction of organic polymers reduces the hydrophilicity of montmorillonite, and combined with the low viscosity and high solubility characteristics of the hyperbranched polymer, the montmorillonite is improved. Due to its compatibility with the asphalt matrix, when it is added to the binder, the modified montmorillonite forms a three-dimensional network structure inside the binder. At high temperatures, it inhibits the movement of asphalt molecules and blocks the entry of oxygen, giving the binder excellent high temperature resistance and aging resistance. The quaternary ammonium salt-terminated antioxidant hyperbranched polymer contains a large number of cavities, phenol structures and active hydrogen. The cavities can stabilize and encapsulate free radicals, phenol can eliminate free radicals, and active hydrogen can be taken by free radicals, playing a role of chain transfer, thereby delaying the reaction of free radical chains during aging and improving the aging resistance of the binder.

[0011] Further, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is prepared by the following steps:

[0012] Step S11, adding antioxidant AB2 monomer and dimethylacetamide to a flask, adding p-toluenesulfonic acid and toluene after stirring, heating to reflux and stirring to react for 8 hours, then reacting at 0.09 MPa and 120° C. for 6 hours, cooling to room temperature, and removing dimethylacetamide by vacuum distillation to obtain an antioxidant hyperbranched polymer;

[0013] Step S12, adding an antioxidant hyperbranched polymer and DMF into a flask, stirring to dissolve, adding sodium hydroxide, and then dropping glycidyl trimethylammonium chloride. After the dropwise addition is completed, stirring and reacting at 50° C. for 24 hours. After the reaction is completed, filtering, and distilling the filtrate under reduced pressure to remove DMF to obtain a quaternary ammonium salt-terminated antioxidant hyperbranched polymer.

[0014] Furthermore, in step S11, the amount ratio of the antioxidant AB2 monomer, dimethylacetamide, p-toluenesulfonic acid and toluene is 10 g: 80-100 mL: 0.4 g: 2.5-3.5 mL, and the antioxidant AB2 monomer is esterified and dehydrated to obtain an antioxidant hyperbranched polymer containing active hydroxyl groups, phenol structures, amide bonds and ester groups;

[0015] Furthermore, in step S12, the dosage ratio of the antioxidant hyperbranched polymer, DMF, sodium hydroxide and glycidyl trimethylammonium chloride is 18-21 g: 100-120 mL: 3.2 g: 16 mL. Under the action of sodium hydroxide, the epoxy group of glycidyl trimethylammonium chloride and the terminal hydroxyl group of the antioxidant hyperbranched polymer undergo a ring-opening reaction, introducing a quaternary ammonium salt structure to obtain a quaternary ammonium salt-terminated antioxidant hyperbranched polymer.

[0016] Furthermore, the steps for preparing the antioxidant AB2 type monomer are as follows:

[0017] Step S21, under nitrogen protection, adding allyl succinic anhydride and dimethylacetamide into a flask, stirring and dissolving, adding diethanolamine under constant stirring at 300 r / min, reacting in an ice-water bath for 1 hour, and then removing dimethylacetamide by reduced pressure distillation to obtain an AB2 type monomer, wherein the molar ratio of allyl succinic anhydride to diethanolamine is 1:1, and based on the fact that the activity of the amino group in diethanolamine is greater than that of the hydroxyl group, the amino group of the diethanolamine is first reacted with allyl succinic anhydride to obtain an AB2 type monomer containing an unsaturated double bond and an amide bond, wherein A is a carboxyl group and B is a hydroxyl group;

[0018] Step S22, adding AB2 type monomer, 4-mercaptophenol, benzoin dimethyl ether and THF into a flask, irradiating with 365nm ultraviolet light after dissolving, stirring for 15-30min, and after the reaction is completed, removing THF by rotary evaporation to obtain an antioxidant AB2 type monomer, wherein the amount ratio of AB2 type monomer, 4-mercaptophenol, benzoin dimethyl ether and THF is 2.45g:1.3g:0.06-0.08g:40-60mL, and under the action of a photoinitiator, the unsaturated double bond of the AB2 type monomer reacts with the thiol group of 4-mercaptophenol, and a phenol structure is introduced into the AB2 type monomer to obtain an antioxidant AB2 type monomer.

[0019] A method for preparing a flame retardant self-adhesive waterproof membrane binder comprises the following steps:

[0020] Heat the asphalt of Type I waterproof membrane to 190-200°C, add aromatic oil and stir evenly, then cool to 180-190°C, add SBS and heat to 190-200°C, stir for 1.5h, add tackifying resin and waste rubber powder, keep warm and stir for 0.5h, then add diethyl aluminum phosphinate and modified montmorillonite, keep warm and stir for 0.5h to obtain a flame retardant self-adhesive waterproof membrane binder.

[0021] Furthermore, the tackifying resin is one or more of coumarone resin, terpene resin and carbon nine resin mixed in any proportion.

[0022] Furthermore, the waste rubber powder is 40-120 mesh waste rubber powder.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention adds aluminum diethylphosphinate and modified montmorillonite as flame retardant components to the waterproof membrane binder. The two have good compatibility with the substrate (aluminum diethylphosphinate molecules contain PC bonds, do not absorb water, and have higher compatibility with the asphalt matrix than polyphosphates and red phosphorus, and the modified montmorillonite has a large interlayer spacing). During the combustion process, the silicate in the modified montmorillonite promotes the carbonization of the polymer and increases the inorganic residue. On the one hand, it protects the matrix and isolates oxygen, and on the other hand, it slows down the release of flammable substances during the thermal decomposition and combustion of the polymer. Aluminum diethylphosphinate plays a flame retardant role in both the gas phase and the condensed phase. Therefore, the self-adhesive waterproof membrane binder prepared by the present invention has high flame retardant properties.

[0025] 2. The present invention adds modified montmorillonite to the binder of the waterproof coiled material, which forms a three-dimensional network structure inside the binder, inhibits the movement of asphalt molecules at high temperatures, and blocks the entry of oxygen, giving the asphalt material excellent high temperature resistance and aging resistance. In addition, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer contains a large number of cavities, phenol structures and active hydrogen inside. The vacancies can stabilize and coat free radicals, phenol can eliminate free radicals, and active hydrogen can be taken by free radicals, playing a role of chain transfer, thereby delaying the reaction of free radical chains during aging and improving the aging resistance of the binder. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] An antioxidant AB2 type monomer, the preparation steps are as follows:

[0029] Step S21, under nitrogen protection, 0.1 mol allyl succinic anhydride and 200 mL dimethylacetamide were added to a flask, stirred and dissolved, and then 0.1 mol diethanolamine was added under constant stirring at 300 r / min, and the mixture was reacted in an ice-water bath for 1 h, and then the dimethylacetamide was removed by reduced pressure distillation to obtain an AB2 type monomer;

[0030] Step S22, add 2.45g AB2 type monomer, 1.3g 4-mercaptophenol, 0.06-0.08g benzoin dimethyl ether and 40-60mL THF into a flask, dissolve and irradiate with 365nm ultraviolet light, stir for 15-30min, and after the reaction is completed, remove THF by rotary evaporation to obtain an antioxidant AB2 type monomer.

[0031] Example 2

[0032] An antioxidant AB2 type monomer, the preparation steps are as follows:

[0033] Step S21, under nitrogen protection, 0.1 mol allyl succinic anhydride and 200 mL dimethylacetamide were added to a flask, stirred and dissolved, and then 0.1 mol diethanolamine was added under constant stirring at 300 r / min, and the mixture was reacted in an ice-water bath for 1 h, and then the dimethylacetamide was removed by reduced pressure distillation to obtain an AB2 type monomer;

[0034] Step S22, add 2.45g AB2 type monomer, 1.3g 4-mercaptophenol, 0.06-0.08g benzoin dimethyl ether and 40-60mL THF into a flask, dissolve and irradiate with 365nm ultraviolet light, stir for 15-30min, and after the reaction is completed, remove THF by rotary evaporation to obtain an antioxidant AB2 type monomer.

[0035] Comparative Example 1

[0036] An AB2 type monomer, the preparation steps are as follows:

[0037] Under nitrogen protection, 0.1 mol succinic anhydride and 200 mL dimethylacetamide were added to the flask, stirred and dissolved, and then 0.1 mol diethanolamine was added under constant stirring at 300 r / min. The mixture was reacted in an ice-water bath for 1 h, and then dimethylacetamide was removed by reduced pressure distillation to obtain an AB2 type monomer.

[0038] Example 3

[0039] A modified montmorillonite is prepared by the following steps:

[0040] Montmorillonite is added into deionized water for dispersion to form a 5wt% suspension, a quaternary ammonium salt-terminated antioxidant hyperbranched polymer is added into a 50wt% ethanol solution for stirring, and then added into the suspension, and reacted at 50°C for 6-8h with stirring. After the reaction is completed, the reaction is centrifuged, and the precipitate is dried at 100°C to constant weight, and ground to obtain modified montmorillonite. The amount of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is 10% of the mass of the montmorillonite, and the amount of the ethanol solution is 10 times the mass of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer. The montmorillonite is Na-based montmorillonite, and the cation exchange capacity is 900-1100 mmol / kg.

[0041] Wherein, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is prepared by the following steps:

[0042] Step S11, add 10g of the antioxidant AB2 monomer of Example 1 and 80mL of dimethylacetamide into a flask, add 0.4g of p-toluenesulfonic acid and 2.5mL of toluene after stirring, heat to reflux and stir to react for 8h, then control the temperature to 0.09MPa, react at 120°C for 6h, after the reaction is completed, cool to room temperature, and remove dimethylacetamide by vacuum distillation to obtain an antioxidant hyperbranched polymer;

[0043] Step S12, add 18g of antioxidant hyperbranched polymer and 100mL of DMF into a flask, stir and dissolve, add 3.2g of sodium hydroxide, then add 16mL of glycidyl trimethylammonium chloride dropwise, after the addition is completed, stir and react at 50°C for 24h, after the reaction is completed, filter, and distill the filtrate under reduced pressure to remove DMF to obtain a quaternary ammonium salt-capped antioxidant hyperbranched polymer.

[0044] Example 4

[0045] A modified montmorillonite is prepared by the following steps:

[0046] Montmorillonite is added into deionized water for dispersion to form a 10wt% suspension, a quaternary ammonium salt-terminated antioxidant hyperbranched polymer is added into a 50wt% ethanol solution for stirring, and then added into the suspension, and the mixture is stirred at 60°C for 8h. After the reaction is completed, the mixture is centrifuged, and the precipitate is dried at 100°C to a constant weight, and then ground to obtain modified montmorillonite. The amount of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is 15% of the mass of the montmorillonite, and the amount of the ethanol solution is 10 times the mass of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer. The montmorillonite is Na-based montmorillonite, and the cation exchange capacity is 900-1100 mmol / kg.

[0047] Wherein, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is prepared by the following steps:

[0048] Step S11, add 10g of the antioxidant AB2 monomer of Example 2 and 100mL of dimethylacetamide into a flask, add 0.4g of p-toluenesulfonic acid and 3.5mL of toluene after stirring, heat to reflux and stir to react for 8h, then control the temperature to 0.09MPa, react at 120°C for 6h, after the reaction is completed, cool to room temperature, and remove dimethylacetamide by vacuum distillation to obtain an antioxidant hyperbranched polymer;

[0049] Step S12, add 21g of antioxidant hyperbranched polymer and 120mL of DMF into a flask, stir and dissolve, add 3.2g of sodium hydroxide, then add 16mL of glycidyl trimethylammonium chloride dropwise, after the addition is completed, stir and react at 50°C for 24h, after the reaction is completed, filter, and distill the filtrate under reduced pressure to remove DMF to obtain a quaternary ammonium salt-terminated antioxidant hyperbranched polymer.

[0050] Comparative Example 2

[0051] A modified montmorillonite, compared with Example 3, the antioxidant AB2 monomer in Example 3 is replaced by the substance in Comparative Example 1, and the remaining raw materials and preparation process are the same as Example 3.

[0052] Comparative Example 3

[0053] A modified montmorillonite, compared with Example 3, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer in Example 3 is replaced by hexadecyltrimethylammonium bromide, and the other raw materials and preparation process are the same as Example 3.

[0054] Example 5

[0055] A flame retardant self-adhesive waterproofing membrane binder, comprising the following raw materials in parts by weight: 100 parts of type I waterproofing membrane asphalt, 5 parts of diethyl aluminum phosphinate, 2 parts of modified montmorillonite of Example 3, 12 parts of SBS (styrene-butadiene-styrene block copolymer), 15 parts of waste rubber powder, 16 parts of aromatic oil, and 10 parts of tackifying resin;

[0056] The preparation steps are as follows:

[0057] Heat the asphalt of Type I waterproof membrane to 190°C, add aromatic oil and stir evenly, then cool to 180°C, add SBS and heat to 190°C, stir for 1.5 hours, add coumarone resin and waste rubber powder, keep warm and stir for 0.5 hours, then add diethyl aluminum phosphinate and modified montmorillonite, keep warm and stir for 0.5 hours to obtain a flame retardant self-adhesive waterproof membrane binder.

[0058] The waste rubber powder is 40-120 mesh waste rubber powder.

[0059] Example 6

[0060] A flame retardant self-adhesive waterproofing membrane binder, comprising the following raw materials in parts by weight: 105 parts of type I waterproofing membrane asphalt, 7 parts of diethyl aluminum phosphinate, 3 parts of modified montmorillonite of Example 4, 14 parts of SBS (styrene-butadiene-styrene block copolymer), 18 parts of waste rubber powder, 18 parts of aromatic oil, and 20 parts of terpene resin;

[0061] The preparation steps are as follows:

[0062] Heat the asphalt of Type I waterproof membrane to 195°C, add aromatic oil and stir evenly, then cool to 185°C, add SBS and heat to 195°C, stir for 1.5 hours, add terpene resin and waste rubber powder, keep warm and stir for 0.5 hours, then add diethyl aluminum phosphinate and modified montmorillonite, keep warm and stir for 0.5 hours to obtain a flame retardant self-adhesive waterproof membrane binder.

[0063] The waste rubber powder is 40-120 mesh waste rubber powder.

[0064] Example 7

[0065] A flame retardant self-adhesive waterproofing membrane binder, comprising the following raw materials in parts by weight: 110 parts of type I waterproofing membrane asphalt, 8 parts of diethyl aluminum phosphinate, 4 parts of modified montmorillonite of Example 4, 16 parts of SBS (styrene-butadiene-styrene block copolymer), 20 parts of waste rubber powder, 20 parts of aromatic oil, and 22 parts of carbon nine resin;

[0066] The preparation steps are as follows:

[0067] Heat the asphalt of Type I waterproof membrane to 200°C, add aromatic oil and stir evenly, then cool to 190°C, add SBS and heat to 200°C, stir for 1.5 hours, add carbon nine resin and waste rubber powder, keep warm and stir for 0.5 hours, then add diethyl aluminum phosphinate and modified montmorillonite, keep warm and stir for 0.5 hours to obtain a flame retardant self-adhesive waterproof membrane binder.

[0068] The waste rubber powder is 40-120 mesh waste rubber powder.

[0069] Comparative Example 4

[0070] A flame retardant self-adhesive waterproof membrane binder. Compared with Example 5, the modified montmorillonite is replaced to form the substance in Comparative Example 2, and the remaining raw materials and preparation process are the same as Example 5.

[0071] Comparative Example 5

[0072] A flame retardant self-adhesive waterproof membrane binder. Compared with Example 5, the modified montmorillonite is replaced to form the substance in Comparative Example 3, and the remaining raw materials and preparation process are the same as Example 5.

[0073] The self-adhesive waterproof membrane binder prepared in Examples 5-7 and Comparative Examples 4-5 was evenly coated on a polyester base, and then covered with a polyethylene film and an anti-adhesive silicone oil isolation film to form a waterproof membrane having, from top to bottom, a 2mm upper protective film, a binder layer composed of a 3mm self-adhesive waterproof membrane binder, a 5mm polyester base, a binder layer composed of a 3mm self-adhesive waterproof membrane binder, and a 3mm lower protective film. The self-adhesive waterproof membrane binder prepared in the examples and comparative examples was tested for limiting oxygen index using a YG-813 oxygen index tester according to the standard "Plastic Combustion Performance Test Method Oxygen Index Method" (GB / T2406-1993). The low-temperature flexibility was tested with reference to Part 14 of GB / T 328-2007 "Test Methods for Building Waterproof Membrane". After that, the membrane was aged for 10 days at 70°C in a forced aging oven, and the low-temperature flexibility was tested again to observe its aging resistance. The test results are shown in Table 1:

[0074] Table 1

[0075] project Example 5 Example 6 Example 7 Comparative Example 4 Comparative Example 5 Binder oxygen index / % 28.2 29.7 30.6 28.0 27.6 Low temperature flexibility before aging -30 -29 -28 -29 -25 Low temperature flexibility after aging -27 -28 -27 -21 -15

[0076] It can be seen from Table 1 that, compared with Comparative Examples 4-5, the self-adhesive waterproof membrane binder prepared in Examples 5-7 not only has high flame retardancy, but also has excellent aging resistance.

[0077] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flame retardant self-adhesive waterproof membrane binder, characterized in that: The invention comprises the following raw materials in parts by weight: 100-110 parts of type I waterproofing coiled material asphalt, 5-8 parts of diethyl aluminum phosphinate, 2-4 parts of modified montmorillonite, 12-16 parts of SBS, 15-20 parts of waste rubber powder, 16-20 parts of aromatic oil, and 10-22 parts of tackifying resin; The modified montmorillonite is prepared by the following steps: The montmorillonite is added to deionized water to disperse and form a suspension, the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is added to an ethanol solution and stirred, and then added to the suspension, and stirred and reacted at 50-60° C. for 6-8 hours to obtain a modified montmorillonite; The quaternary ammonium salt-terminated antioxidant hyperbranched polymer is prepared by the following steps: Step S11, mixing an antioxidant AB2 monomer and dimethylacetamide, adding p-toluenesulfonic acid and toluene after stirring, heating to reflux and stirring to react for 8 hours, and then reacting at 0.09 MPa and 120° C. for 6 hours to obtain an antioxidant hyperbranched polymer; Step S12, mixing the antioxidant hyperbranched polymer and DMF, stirring and dissolving, adding sodium hydroxide, and then dripping glycidyl trimethylammonium chloride, after the dripping is completed, stirring and reacting at 50° C. for 24 hours to obtain a quaternary ammonium salt-terminated antioxidant hyperbranched polymer; The steps for preparing the antioxidant AB2 type monomer are as follows: Step S21, under nitrogen protection, allyl succinic anhydride and dimethylacetamide are mixed, diethanolamine is added under stirring, and the mixture is reacted under ice-water bath for 1 hour to obtain AB2 type monomer; Step S22, mixing AB2 type monomer, 4-mercaptophenol, benzoin dimethyl ether and THF, dissolving and irradiating with 365 nm ultraviolet light, stirring for 15-30 minutes, to obtain an antioxidant AB2 type monomer.

2. The flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: The content of montmorillonite in the suspension is 5-10wt%, the mass fraction of the ethanol solution is 50%, the amount of the quaternary ammonium salt-terminated antioxidant hyperbranched polymer is 10-15% of the mass of the montmorillonite, and the montmorillonite is Na-based montmorillonite.

3. The flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: In step S11, the dosage ratio of the antioxidant AB2 monomer, dimethylacetamide, p-toluenesulfonic acid and toluene is 10 g: 80-100 mL: 0.4 g: 2.5-3.5 mL.

4. The flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: In step S12, the dosage ratio of the antioxidant hyperbranched polymer, DMF, sodium hydroxide and glycidyl trimethylammonium chloride is 18-21 g: 100-120 mL: 3.2 g: 16 mL.

5. The flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: The molar ratio of allylsuccinic anhydride to diethanolamine is 1:

1.

6. The flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: The usage ratio of AB2 type monomer, 4-mercaptophenol, benzoin dimethyl ether and THF is 2.45g:1.3g:0.06-0.08g:40-60mL.

7. The method for preparing a flame retardant self-adhesive waterproof membrane binder according to claim 1, characterized in that: The following steps are involved: Heat the asphalt of Type I waterproof membrane to 190-200°C, add aromatic oil and stir evenly, then cool to 180-190°C, add SBS and heat to 190-200°C, stir for 1.5h, add tackifying resin and waste rubber powder, keep warm and stir for 0.5h, then add diethyl aluminum phosphinate and modified montmorillonite, keep warm and stir for 0.5h to obtain a flame retardant self-adhesive waterproof membrane binder.

Citation Information

Patent Citations

  • Flame-retardant self-adhesive waterproof membrane adhesive, its preparation method, and waterproof membrane prepared therefrom.

    CN110760289B

  • Antistatic anticorrosive and antirust coating, preparation method and application thereof

    CN107141971A

  • Self-adhesive waterproofing coiled material cementing material, its preparation method and waterproofing coiled material prepared from self-adhesive waterproofing coiled material cementing material

    CN107474793A